IMPROVEMENT OF THE DESIGN OF A DOMESTIC REFRIGERATOR WITH THE AIM OF REDUCING HEAT LOSSES - KRETIUK, VADYM; SOKOLAN, IULIIA; MAIDAN, PAVLO; NEIMAK, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
From October 2025, in accordance with Resolution No. 1181 of the Cabinet of Ministers of Ukraine, new energy efficiency classes for household appliances will come into force in Ukraine, which comply with the new European energy efficiency standard. Under the new standard, household appliances that previously had an A+++ energy efficiency class will now correspond to energy efficiency class D. The issue of improving the existing designs of household appliances, namely the most common two-compartment refrigerators, in order to reduce heat loss and thereby increase energy efficiency, is becoming increasingly relevant. The paper presents improvements to the design of a two-compartment household refrigerator, namely: the addition of a 20 mm thick vacuum-insulated panel on the front wall of the refrigerator, adding a 30 mm thick VIP to the rear wall of the refrigerator with a reduction in the thickness of the rear wall of the refrigerator from 80 to 60 mm in order to reduce the loss of useful volume in the refrigerator and freezer compartments, reducing the gap between the walls of the refrigerator and VIP, which will increase the heat path and reduce the width of thermal bridges, increasing the length of the VIP, moving the compressor compartment from the bottom of the refrigerator to the top. The COMSOL Multiphysics software package was used to model and calculate heat losses. The introduction of these improvements allows, according to the modelling results, to reduce heat losses from 33 to 65% in individual structural elements of the refrigerator, and total heat losses are reduced by 47%. In addition to the proposed improvements, which reduce heat loss in the refrigerator by 42%, it is also proposed to change the design of the gasket. The paper proposes two gasket designs – with round and diamond-shaped chambers. A gasket with round chambers reduces heat loss by 33 to 38%, and a gasket with diamond-shaped chambers reduces it by 38 to 39%. Considering that the manufacture of a gasket with round chambers reduces material consumption by 7%, while the material consumption for manufacturing a gasket with diamond-shaped chambers is reduced by 25%, the most optimal gasket option would be a gasket with diamond-shaped chambers.